2017
DOI: 10.1038/nrm.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Splicing and transcription touch base: co-transcriptional spliceosome assembly and function

Abstract: Several macromolecular machines collaborate to produce eukaryotic messenger RNA. RNA polymerase II (Pol II) translocates along genes that are up to millions of base pairs in length and generates a flexible RNA copy of the DNA template. This nascent RNA harbours introns that are removed by the spliceosome, which is a megadalton ribonucleoprotein complex that positions the distant ends of the intron into its catalytic centre. Emerging evidence that the catalytic spliceosome is physically close to Pol II in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
293
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(302 citation statements)
references
References 184 publications
(269 reference statements)
8
293
0
1
Order By: Relevance
“…The C-terminal domain (CTD) of polymerase II has been shown to bind polymers of LCD proteins [63]; as other studies reported the interaction of the CTD with U2AF 65 [64][65][66], we can hypothesize that U2AF 65 assemblies play a role in bridging the splicing and the transcription machineries. LLPS of U2AF 65 could also reduce diffusion from transcription sites, as recently proposed more generally for splicing factors harboring LCD [67]. This is supported by our results and the observation by Carmo-Fonseca and colleagues that the RS domain is required for U2AF 65 accumulation at transcription sites [49].…”
Section: Rs Domain-dependent Formation Of Macromolecular Assembliessupporting
confidence: 91%
“…The C-terminal domain (CTD) of polymerase II has been shown to bind polymers of LCD proteins [63]; as other studies reported the interaction of the CTD with U2AF 65 [64][65][66], we can hypothesize that U2AF 65 assemblies play a role in bridging the splicing and the transcription machineries. LLPS of U2AF 65 could also reduce diffusion from transcription sites, as recently proposed more generally for splicing factors harboring LCD [67]. This is supported by our results and the observation by Carmo-Fonseca and colleagues that the RS domain is required for U2AF 65 accumulation at transcription sites [49].…”
Section: Rs Domain-dependent Formation Of Macromolecular Assembliessupporting
confidence: 91%
“…Notably, there is a functional relationship between the transcriptional and the splicing machineries, as evidenced by the role of splicing factors, such as TCERG1, also known as CA150 (Suñ é & Garcia-Blanco, 1999) and SRSF2 (Lin et al, 2008), in stimulating transcriptional elongation. Interestingly, a role for transcription elongation rate influencing splicing fidelity and cotranscriptionality was also observed in yeast (Herzel et al, 2017;Aslanzadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…The co-transcriptional nature of pre-mRNA splicing led to the suggestion that the rate of transcription elongation acts to control AS in mammalian cells (Beyer & Osheim, 1988;Roberts et al, 1998;Pandya-Jones & Black, 2009). Interestingly, a role for transcription elongation rate influencing splicing fidelity and cotranscriptionality was also observed in yeast (Herzel et al, 2017;Aslanzadeh et al, 2018). Interestingly, a role for transcription elongation rate influencing splicing fidelity and cotranscriptionality was also observed in yeast (Herzel et al, 2017;Aslanzadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of co-transcriptional splicing has profoundly increased our understanding of how transcription is intricately intertwined with RNA processing (reviewed in 114 ). Upon heat shock, both splicing and polyadenylation have been shown to be globally reduced 115117 .…”
Section: Co-transcriptional Processingmentioning
confidence: 99%